MENINGKATKAN KESADARAN LINGKUNGAN MELALUI PUBLIC SPEAKING BAGI SISWA SMAN 7 BEKASI - Ambarsari, Dewi (Jurnal Abdi Insani, 2024)
Increasing environmental awareness and maintaining environmental sustainability is one of the goals in sustainable development. This needs to be conveyed to students so that they understand the importance of preserving the environment and are able to convey effective and persuasive messages to others through public speaking. Students as a young generation who can create positive changes need to have public speaking skills to communicate this real action. The purpose of this activity is to increase environmental awareness and educate students about environmental issues and improve public speaking skills as an effort to convey environmental messages to others and the wider community. This activity was carried out at SMAN 7 Bekasi City with 40 students participating. PkM activities are carried out through three parts, namely preparation, implementation and evaluation. In the implementation stage, students were given material about the importance of increasing environmental awareness and how to convey environmental communication to others through public speaking so that students are able and brave to convey environmental messages well. The results of the activity show that students have more in-depth knowledge about environmental communication, how to maintain and preserve the environment and are able to compose interesting environmental messages through public speaking to convey environmental messages to the wider community. This is known from the results of the activity evaluation. Evaluation activities are carried out to ensure participants have deeper knowledge about environmental conservation and are able to compose interesting environmental messages through public speaking.  Students conveyed the need for further activities on environmental communication and public speaking training so that students as a young generation have high environmental awareness and have good public speaking skills. This Community Service activity is able to increase environmental awareness and be able to provide public speaking skills to students, which will be used in conveying environmental messages.